(untitled) (London Journal of Medical and Health Research, 2025)
Background: The increasing reliance on ultra-processed foods (UPFs) among adolescents has emerged as a global nutritional concern. UPFs are typically energy-dense, rich in unhealthy fats, sugars, and additives, while being poor in micronutrients. Excessive intake of such foods has been linked to obesity, metabolic dysfunction, and early pubertal onset. Menarche, a critical milestone in female reproductive development, is influenced by nutritional and environmental factors. However, evidence from Indian contexts, particularly rural and semi-urban regions, remains limited. Objective: This study aimed to examine the relationship between dietary fat intake from UPFs, body mass index (BMI), and menstrual health indicators—specifically age at menarche and the occurrence of early menarche—among school-going adolescent girls in the Midnapore district of West Bengal, India. Methods: A cross-sectional survey was conducted among adolescent girls (N = 232) using a structured questionnaire covering socio-demographic characteristics, dietary habits, anthropometric measurements, and menstrual history. Nutrient intake, with a focus on fat consumption from UPFs was estimated and BMI was computed using WHO criteria. Descriptive statistics, linear regression, and binary logistic regression analyses were employed to assess associations. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated for early menarche (< 12 years). Results: The mean age at menarche in the study population was 12.45 ± 0.98 years. Nearly one in five participants (≈22%) experienced early menarche. High dietary fat intake (≥ 75th percentile, proxy for UPF consumption) was significantly associated with early menarche (OR = 1.64, 95% CI: 1.10–2.46). Linear regression analyses indicated that dietary fat intake was inversely related to monarchical age (β = -0.003, p < 0.05), independent of BMI. Furthermore, BMI exhibited a significant negative association with age at menarche (β = -0.020, p < 0.01), suggesting that overweight girls tended to attain menarche earlier. Conclusion: The findings highlight a strong association between ultra-processed food consumption, elevated BMI, and earlier onset of menarche in adolescent girls. Given the potential long-term implications—such as increased risk of menstrual irregularities, metabolic disorders, and reproductive health challenges—public health interventions promoting nutritional literacy, healthier dietary alternatives, and lifestyle modifications are urgently warranted in school and community settings.